Maltese in London, 1966-1969: Maltese men in London, 1966-1968 - Dench, Geoff (UK Data Service, 1976)
The purpose of this study was to provide measures of the overall state of community articulation and participation among Maltese settlers living in Inner London, and general indications of the character of the settlement.